2014
DOI: 10.1016/j.sjopt.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional MRI study: Safety of short versus long needle peribulbar anesthesia

Abstract: There is a larger structure-free space at a depth of 12.5 mm than at 25 mm. Therefore, the inference is that a needle inserted in the infero-temporal zone to a depth of 12.5 mm is less likely to injure the eyeball or extra-ocular muscles than one advanced to 25 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Patients' data sets that showed signs of peribulbar anesthesia were excluded from the final analysis. However, ElKhamary et al 24 observed the effect of different peribulbar anaesthesia techniques, and they did not observe any morphologic changes of the globe in their MRIs, but it has to be mentioned that their focus of the study was the peribulbar region.…”
Section: Discussionmentioning
confidence: 96%
“…Patients' data sets that showed signs of peribulbar anesthesia were excluded from the final analysis. However, ElKhamary et al 24 observed the effect of different peribulbar anaesthesia techniques, and they did not observe any morphologic changes of the globe in their MRIs, but it has to be mentioned that their focus of the study was the peribulbar region.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of injury by long needles increases particularly in patients with shallow orbits [4]. The use of needles with shorter lengths (12 to 15 mm) has been reported in the literature [9][10][11][12][13][14][15][16][17][18], with varying results of efficacy and safety compared with the standard PBA technique. The present study thus aimed to compare the efficacy and safety of using a 12mm needle to the standard 25mm needle in performing PBA at the medial canthus in cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The injection of a small volume of local anesthetic (5-6.5 ml) was demonstrated to surround the eye globe and produce analgesia. The higher need for anesthetic supplementation in PBA with long needles may be explained by the potential passing of the needle into the inferior orbital floor which causes a reduction of the spread of local anesthetic around the eye globe [9,19]. The rate of requiring anesthetic supplementation while performing PBA with short needles varied widely among the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI has been used to assess the risks of peribulbar anaesthesia to extra ocular muscles in the infero-temporal quadrant (myopic patients were excluded) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%